The Art of Color : The subjective experience and objective rationale of color - Itten, Johannes; Reinhold Publishing Corporation, New York (Ravensburg : Otto Maier Verlag, 1961)
Mondrian, Piet ; Picasso, Pablo ; Renoir, Auguste ; Monet, Claude ; Cézanne, Paul ; van Gogh, Vincent ; Matisse, Henri ; Klee, Paul ; Seurat, Georges ; etc.
Engels
boek
Keywords: Itten, Johannes